The Confidence Game : The Psychology of the Con and Why We Fall for it Every Time - Konnikova, Maria (Edinburgh Canongate Publishing, 2016)
Monografie over de psychologie van oplichting en waarom we er iedere keer weer intrappen
Include Notes and Index
Keywords: Swindlers and swindling -- Fraud -- Criminal psychology